Salivary gland mucoceles: A clinical study of 103 cases (Mustansiria Dental Journal, 2018)
Mucocele is a tissue swelling composed of pooled mucus that escaped into the connective tissue from a severed salivary excretory duct (extravasated).In the present study 103 cases of mucoceles reviewed from the records of patients at the Department of the Oral Pathology, faculty of Dentistry , Baghdad University over 11 years period ( 1982-1992). Mucoceles were statically analyzed according to age, gender , site of occurrence and type.It was found that a greater number of mucoceles cases 37(36%) occur in patients at 2nd decade of age followed by 29(28.2) of cases occurred in 3rd decade of age. Mucoceles were occurred more in males than females 57(55.2%) ,46 (44.8%),respectively.Lower lip was the predominant site for occurrence of mucocele 84(81.6%) followed by the floor of the mouth 12(11.7%).The most frequent type of mucocele was of extravasated type100(97.1%) whereas it was only 3(2.9%)for mucous retention type.Key words: Mucocele, Salivary gland cyst.